FIFA Women's World Cup 2011: Pre-Competition Medical Assessment of female referees and assistant referees. Issue 3 (12th September 2012) - Keller, Dagmar I; Bizzini, Mario; Feddermann, Nina; Junge, Astrid; Dvorak, Jiri
Abstract : Background: Precompetition screening was implemented for male referees during the 2010 Fédération Internationale de Football Association (FIFA) Word Cup. In contrast, female football referees have been neglected in this respect although they experience similar physical work loads compared to male referees. Methods: The standardised football-specific Pre-Competition Medical Assessment (PCMA) was performed in 51 referees and assistant referees selected for the 2011 FIFA Women's World Cup. Results: Family history for sudden cardiac death (SCD) was positive in four referees (7.8%), but cardiac examinations did not reveal any pathological findings. Training-unrelated ECG changes were identified in three referees (5.9%), all without correlates in echocardiography or clinical examination. Most common echocardiography findings (66.6%, n=34) were asymptomatic tricuspid and mitral regurgitations. Conclusions: During the present screening, no elite female referee was identified being at risk for SCD, and no referee had to be excluded from participating in the 2011 FIFA Women's World Cup.